The The Research Status of Neurological Surgery Residents; A Survey of Iranian Residency Programs: Research Status of Iranian Neurosurgery Residents - Khosravi, Mohammad Hossein; Mehri, Afsaneh; Jabbaripour, Sama; Kazemi, Fatemeh; Khosravi, Zahra; Ahmadi, Sayedali (International Clinical Neuroscience Journal, 2021)
Background: Research activities promote the appreciation for evidence-based medicine (EBM), quality patient care and clinical competence of resident physicians. We decided to investigate the research background of Iranian neurological surgery residents and their attitude toward research through a survey. Methods: This cross-sectional study was done on Iranian neurological surgery resident physicians between February and April 2020. We provided an online survey, including 13 questions, using Google form and then sent the link to survey via WhatsApp application. Following the first post, two more reminders were sent to the groups after 2 and 4 weeks. Results: Responses were received from 89 respondents from which about 88% used to spend two hours or less per week for research. Almost equal numbers of resident physicians chose academic position (n = 43) or private practice (n = 39) as their future job. Only seven respondents stated immigration for assumed future job position. Clinical research (47%) was the most frequent type of research done by participants and clinical research education (43.2%) during medical school was the most common way of obtaining research experience. Agreement with doing research during residency program (45.6%) was more than disagreement (22.4%) and neutral attitude (32%). Conclusion: There is a low tendency among Iranian neurological surgery residents for conducting research projects during their programs. Lack of a proper research curriculum, heavy clinical duties and consequent shortage of time as well as insufficient encouraging points, are the main reasons. Designing a research plan for residency programs may successfully increase the research involvement rate.